2013
DOI: 10.1177/0961000613476728
|View full text |Cite
|
Sign up to set email alerts
|

Competencies required by special librarians: An analysis by educational levels

Abstract: This paper presents the results of a study conducted with the aim of identifying competencies needed by special librarians in Iran at three different levels of library and information science education. A list of competencies was initially identified from the literature and 21 semi-structured interviews with managers of special libraries in Iran. Then, a panel of experts was employed to validate 122 competency statements by using a seven-point Likert type scale. The results demonstrated that the panelists vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 14 publications
3
18
0
Order By: Relevance
“…As the literature suggests, the role of librarians has been evolving (Robati and Singh, 2013). Previously, librarians were mainly responsible for managing library resources.…”
Section: Librarians' Teaching Competenciesmentioning
confidence: 99%
See 1 more Smart Citation
“…As the literature suggests, the role of librarians has been evolving (Robati and Singh, 2013). Previously, librarians were mainly responsible for managing library resources.…”
Section: Librarians' Teaching Competenciesmentioning
confidence: 99%
“…The substantial impact of the information revolution has threatened traditional library services and practices globally (Womboh, 2008). To address the changes to librarians’ work environments and settings, brought on by this revolution to, a new set of competencies are emerging (Pinfield, 2001; Robati and Singh, 2013; Womboh, 2008). It appears that the knowledge and skills librarians used to need for the provision of traditional library services are not enough to cope with the ongoing information revolution (Byatt et al, 2015; Fourie, 2003).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The SLA defines the necessary professional competencies as managing information organizations, managing information resources, managing information services and applying information tools and technologies. A study by Robati and Singh (2013) reported that information technology (IT) skills were the most highly valued skills in special librarians, followed by information organization, research and communication and interpersonal skills. The study cited the importance of the "ability to work with and improve an integrated library management system, use search engines and search strategies, use IT to acquire, organize, and disseminate information, work with information banks, and lead information services to digitization" (Robati and Singh, 2013, p. 127).…”
Section: New and Emerging Roles For Librariansmentioning
confidence: 99%
“…Although definitions vary, most LIS literature agrees that 'competencies' are, more or less, a combination of skills, knowledge and attitudes (Peyvand Robati & Singh, 2013). According to the European e-Competence Framework (2014, p. 11), a competence is "a demonstrated ability to apply knowledge, skills and attitudes to achieving observable results".…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to the European e-Competence Framework (2014, p. 11), a competence is "a demonstrated ability to apply knowledge, skills and attitudes to achieving observable results". The inclusion of attitudes as an aspect of competencies is sometimes contested because attitudes are far less visible and measurable than skills or knowledge (Peyvand Robati & Singh, 2013). 'Competency profiling' are methods for identifying the skills, knowledge and attitudes needed in a particular role (Shellabear, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%